Pengaruh Pemberian Dosis POC ( Pupuk Organik Cair ) Limbah Kulit Kopi Dan Media Tanam Terhadap Pertumbuhan Benih Sawi Caisim (Brassica chinensis var. parachinensis) - Sri Hartanti, Dyah Ayu; Mubarok, Aldi; Zuhria, Siti Aminatuz (Universitas PGRI Adi Buana Surabaya, 2023)
This study aims to determine the effect of doses of Liquid Organic Fertilizer coffee peels and planting media on the growth of Caisim mustard seeds (Brassica chinensis var. parachinensis). This type of research is quantitative. The design used in this study was a randomized block design (RBD) with 2 factor treatment design, namely the addition factor of liquid organic fertilizer dose and the type of planting medium, which consisted of 5 treatment levels with 2 replications. So that 10 experimental units were obtained for each type of planting medium, so that 30 polybags were found with experimental units including 0 ml POC (P1), 5 ml POC (P2), 10 ml POC (P3), 15 ml POC (P4), 20 ml POC (P5) and soil (M1), cocopeat (M2), roasted husks (M3). Parameters observed include stem length, root length, number of roots and number of leaves. Data analysis technique used ANOVA test of variance at 5% level and DMRT follow-up test at 5% level. The results of the ANOVA test showed that the effect of dosing of organic fertilizers was not significantly different on the growth of mustard seeds, whereas the effect of the planting media on the growth of mustard seeds was significantly different and for the planting medium which had the maximum effect was the M3 treatment (burnt husk planting medium) indicated by the highest mean value of several DMRT tests for other M (planting media) treatments.